Community-level impacts of AIDS-related mortality: panel survey evidence from Zambia - Jayne, Thomas S.; Chapoto, Antony; Byron, Elizabeth; Ndiyoi, Mukelabai; Hamazakaza, Petan; Kadiyala, Suneetha; Gillespie, Stuart (Oxford University Press, 2006)
Governments and development agencies require accurate information on the impacts of increased mortality rates caused by AIDS on the agricultural sector and rural livelihoods. Several previous studies have estimated the effects of prime-age mortality on afflicted households in relation to non-afflicted households... Using nationally representative household panel data from rural Zambia, we measure the effects of prime-age adult mortality rates on changes in a set of community level welfare indicators... In general, the findings of this study offer limited support for the view that prime-age mortality is decimating agrarian-based economic systems in regions that are hard-hit by the HIV/AIDS pandemic. However, this in no way implies that great hardship is not being wrought by the disease in ways that are not measured in this data, and further research from other areas and/or time periods will be necessary before strong conclusions can be generated about the effects of AIDS-related mortality in regions of the world where prevalence rates are very high.